2016
DOI: 10.1186/s12936-016-1138-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity of malaria in Ghana: a cross-sectional study on the association between urbanicity and the acquisition of immunity

Abstract: BackgroundMalaria incidence has declined considerably over the last decade. This is partly due to a scale-up of control measures but is also attributed to increasing urbanization. This study aimed to analyse the association between malaria and urbanization and the effect of urbanicity on the acquisition of semi-immunity.MethodsIn 2012, children with fever presenting to St Michael’s Hospital Pramso/Ghana were recruited. The malaria-positive-fraction (MPF) of fever cases was calculated on community-level to appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The prevalence of maternal parasitaemia appears to remain relatively higher in the northern savannah transmission zone in spite of the seeming general decline described and this may have to do with the characteristic seasonal malaria transmission pattern, the hot weather that may deter consistent bed net utilization and possibly slower urbanized development compared to Accra in the coastal belt [ 55 , 56 ]. It has been reported that part of the burden of malaria infection in pregnancy results from pre-conception infection [ 57 ] and it is possible this phenomenon may be playing a role in Ghana, especially in the northern zone with marked seasonal transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of maternal parasitaemia appears to remain relatively higher in the northern savannah transmission zone in spite of the seeming general decline described and this may have to do with the characteristic seasonal malaria transmission pattern, the hot weather that may deter consistent bed net utilization and possibly slower urbanized development compared to Accra in the coastal belt [ 55 , 56 ]. It has been reported that part of the burden of malaria infection in pregnancy results from pre-conception infection [ 57 ] and it is possible this phenomenon may be playing a role in Ghana, especially in the northern zone with marked seasonal transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier study was in a semi-rural area and the latter in an urban area. Urban development and possibly greater IPTp-SP uptake on account of presumed higher levels of education characteristic of urban settlements [ 55 , 58 , 59 ] may have contributed to the low prevalence in that location even though higher education does not always translate into better IPTp uptake [ 60 ]. The means of detection of placental malaria infection could have affected the prevalence reported.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in Ghana for a number of years [33, 45]. Among households with access, one possible reason for non-use among the urban population is a lower perceived risk of disease from malaria, especially as disease prevalence is much lower in urban areas than rural ones [46, 47]. This is attributed mainly to two things: first, decreases in breeding sites and resting places for mosquitoes, partly attributable to source management and larviciding which has severely diminished the mosquito population, and second, urban households in Ghana have used alternative protective measures such as house screening (over 80% of the urban households in Accra have window screens), aerosol sprays, and mosquito coils for several years [48].…”
Section: Discussionmentioning
confidence: 99%
“…We identified studies covering urban environments in 31 sub-Saharan African countries, plus four review articles with a focus on sub-Saharan Africa as a whole. Two studies were conducted in Angola [14,15], three in Benin [16][17][18], one in Botswana [19], seven in Burkina Faso [20][21][22][23][24][25][26], five in Cameroon [16,25,[27][28][29], one in Chad [30], two in Cote d'Ivoire [25,31], three in the Democratic Republic of Congo [15,25,32], three in Eswatini [25,33,34], seven in Ethiopia [25,[35][36][37][38][39][40], seven in Ghana [25,[41][42][43][44][45][46], two in Guinea [25,47], two in Guinea-Bissau [48,49], fourteen in Kenya [12,…”
Section: Study Characteristicsmentioning
confidence: 99%